Past and Future of Neurotrophic Growth Factors Therapies in ALS: From Single Neurotrophic Growth Factor to Stem Cells and Human Platelet Lysates - Gouel, Flore; Rolland, Anne-Sophie; Devedjian, Jean-Christophe; Burnouf, Thierry; Devos, David (Frontiers in Neurology, 2019)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease that typically results in death within 3 to 5 years after diagnosis. To date, there is no curative treatment and therefore an urgent unmet need of neuroprotective and/or neurorestorative treatments. Due to their spectrum of capacities in the central nervous system, -e.g. development, plasticity, maintenance, neurogenesis-, neurotrophic growth factors (NTF) have been exploited for therapeutic strategies in ALS for decades. In this review we present the initial strategy of using single NTF by different routes of administration to the use of stem cells transplantation to express a multiple NTFs-rich secretome to finally focus on a new biotherapy based on the human platelet lysates, the natural healing system containing a mix of pleitropic NTF and having immunomodulatory function. This review highlights that this latter treatment may be crucial to power the neuroprotection and/or neurorestoration therapy requested in this devastating disease.